Comparative Evaluation of Vitamin and Mineral Composition of Composite Cakes Fortified with Cocoyam, Plantain, and Bambara Nut Flour Blends - Eunice Kanayo Agidi; Diana Oritsegbubemi Arubayi; Azonuche, Juliana Ego; Omolara Bosede Ogbonyomi (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The study was conducted in the Food and Nutrition Laboratory, Delta State University, using an experimental research design to develop and evaluate cakes from wheat, cocoyam, plantain, and bambara nut composite flours at varying substitution ratios. A total population of 185 staff and students formed the study group, while 15 purposively selected judges (7 staff, 8 students) assessed the cakes. Data were collected using a 9-point Hedonic scale for sensory evaluation and a 5-point scale for shelf-life monitoring. Validity was ensured by expert review, and reliability yielded coefficients of 0.81 and 0.88. Nutritional composition, sensory attributes, and shelf life were analyzed using AOAC methods and ANOVA (p≤0.05). Results showed that composite cakes contained significantly higher (p≤0.05) levels of essential vitamins and minerals compared to the control. The vitamin and mineral composition of composite cakes showed clear improvements over 100% wheat flour (WF). Vitamin A ranged from (0.987–1.983 mg/100g), highest in WCPB3 (1.983) and lowest in WF (0.987). Vitamin B1 varied (0.235–0.487 mg/100g), with WCPB4 highest (0.487) and WF lowest (0.235). Vitamin B12 ranged (0.011–0.017 mg/100g), peaking in WCPB5 (0.017) and lowest in WF (0.011). For minerals, calcium ranged (34.225–67.928 mg/100g), iron (2.884–3.971), magnesium (16.285–20.676), phosphorus (60.730–74.066), and zinc (1.571–1.918). Composite samples, especially WCPB5 and WCPB6, consistently outperformed WF, showing significant (p≤0.05) nutritional enhancement. The findings highlight the potential of cocoyam, plantain, and bambara nut as viable alternatives for fortifying baked products, thereby contributing to improved nutrition, food security, and reduced dependence on imported wheat flour